2021
DOI: 10.1002/htj.22157
|View full text |Cite
|
Sign up to set email alerts
|

Spectral simulation to investigate the effects of nanoparticle diameter and nanolayer on the ferrofluid flow over a slippery rotating disk in the presence of low oscillating magnetic field

Abstract: This article explores the impacts of the solid–liquid interfacial layer and nanoparticle diameter on the unsteady ferrous‐water nanoliquid flow over a spinning disk. The existence of velocity slip is presumed on the disk. Additionally, the low oscillating magnetic field effect is included to extract the hydrothermal consequences of the problem. Shliomis theory has been presented to verbalize the foremost equations of the mentioned flow problem. The similarity transformation renders the dimensionless equations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Temperature outlines of nanofluid are reduced when diameter of nano‐sized particles dp ${d}_{p}$ enhances. The previous studies 9 got an identical effect. Imprints are well distinctive inside boundary layer.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Temperature outlines of nanofluid are reduced when diameter of nano‐sized particles dp ${d}_{p}$ enhances. The previous studies 9 got an identical effect. Imprints are well distinctive inside boundary layer.…”
Section: Resultssupporting
confidence: 56%
“…The radiative heat flux is given by qr=4σ*3k*T4r)(=16σ*3k*T3Tr ${q}_{r}=-\frac{4{\sigma }^{* }}{3{k}^{* }}\frac{\partial {T}^{4}}{\partial r}\left(=\frac{16{\sigma }^{* }}{3{k}^{* }}{T}^{3}\frac{\partial T}{\partial r}\right)$. And for nanofluid μnf,ρnf,false(ρcpfalse)nf ${\mu }_{nf},{\rho }_{nf},{(\rho {c}_{p})}_{nf}$ are respectively defined by 9 }μnf=μf(1ϕ)2.5,ρnf=false(1ϕfalse)ρf+ϕρs,(ρcp)nf=false(1ϕfalse)(ρcp)f+ϕ(ρcp)s. $\left.\begin{array}{c}{\mu }_{nf}={\mu }_{f}{(1-\phi )}^{-2.5},{\rho }_{nf}=(1-\phi ){\rho }_{f}+\phi {\rho }_{s},\\ {(\rho {c}_{p})}_{nf}=(1-\phi ){(\rho {c}_{p})}_{f}+\phi {(\rho {c}_{p})}_{s}\end{array}\right\}.$…”
Section: Mathematical Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related articles are in. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Coming to the laws of thermodynamics it is seen that the second law of thermodynamics is much more reliable than the first law of thermodynamics owing to its limitation of efficiency in heat transfer in engineering systems. 58 This second law is used for minimizing the irreversibility of thermal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Acharya et al 28 reported the temperature behaviour under in radiated nanofluid by using thermal conductance model comprising the influences of nanolayer and diameter. Other recent studies for heat transfer under solid–liquid interfacial layer, solar energy and ferro fluid flow slippery geometry were described in 29 31 .…”
Section: Introductionmentioning
confidence: 99%